Mitigating production risk through stress tolerant varieties may be more appealing to farmers than index-insurance” - CGIAR Research Program on Maize (2020)
Breeding for Stress tolerance can be a good substitute for index insurance products, which is yet to be a self-sustaining and viable options for mitigating production risk by smallholders.